2012
DOI: 10.3329/bjo.v18i1.10408
|View full text |Cite
|
Sign up to set email alerts
|

Importance of nasal endoscopy for the evaluation of epistaxis

Abstract: Abstract:Objective : To evaluate the effectiveness of nasal endoscopy in cases of epistaxis. within an emergency setting, some are complex and may require specialist intervention. In most of the patients proper diagnosis is not possible without nasal endoscopy. Majority of the patients attending emergency department with this symptom are managed conservatively to control bleeding. Thorough clinical examination (including anterior and posterior rhinoscopy) do not reveal any abnormality in most of the cases. Sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
1
0
Order By: Relevance
“…The nasal endoscope has been a boon to the otolaryngologist, since it not only helps in the proper visualization of the bleeding sites, but also offers a direct and an early facility of the treatment to an area that was once difficult to access [3,7,[17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…The nasal endoscope has been a boon to the otolaryngologist, since it not only helps in the proper visualization of the bleeding sites, but also offers a direct and an early facility of the treatment to an area that was once difficult to access [3,7,[17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…We found that 14 (70 %) patients were male and 6 (30 %) patients were female with male: female ratio of (2,3:1) Gulshan et al, found that the percentage of male patients and female patients were 67.4% and 32.5% respectively with male to female ratio is 2:1 and this goes with our results (6). Ritman Ray et al, found in their study that male patients also outnumbered the female patients with male to female ratio of 2.1:1 (7) This sex difference can be explained by the fact that male patient are more exposed to environmental factors than female patients , and also the higher prevalence of cardiovascular diseases among male patients .…”
mentioning
confidence: 88%
“…Out of 20 patients enrolled in our study , we found that 15 patients have certain systemic diseases ,also with antiplateplate or anticoagulant drug intake . Table 4 shows distribution of systemic diseases and drug ingestion in those 15 patients (7).…”
mentioning
confidence: 99%